Biosynthesis of S-Methylcysteine in Radish Leaves(1) - Thompson, John F. (1966)
Investigation on the biosynthesis of S-methyl-L-cysteine in radish leaves has shown that it is formed by the methylation of cysteine. This conclusion is based on: A) the relatively high recovery of radioactivity in methylcysteine sulfoxide after the administration of cysteine or methyl-labeled methionine to radish leaves; B) the nearly complete recovery of label from methyl-labeled methionine in the methyl group of methylcysteine sulfoxide; and C) the similarity in the ratio of tritium to (14)C in methylcysteine sulfoxide and in its methyl group to this ratio in the methyl group of methionine given to radish leaves. Direct evidence for the synthesis of methylcysteine in radishes was obtained for the first time. Conclusive evidence against the formation of methylcysteine from serine and a thiomethyl group from methionine as suggested for garlic was the more efficient incorporation of the methyl group of methionine as compared to the sulfur atom into methylcysteine sulfoxide.